Pseudo social media classrooms: Sharing control with “the audience” as an academic literacy practitioner on an online platform - Louw, Louri; Sparks, Linda (Journal for Language Teaching, 2023)
In the academic literacy (AL) class, fostering engagement between educators and students in the online environment is challenging. However, sharing control in the online classroom provides a solution which assists in overcoming this, as well as engaging students academically. Interestingly, because students are familiar with game shows and social media, where they are used to sharing opinions, simulation of this in the online class may provide a solution to participation on an academic platform. In popular game shows, there is a powershift when the audience gains more control through participation, which ultimately improves ratings (Enli & Ihlebæk, 2011). The same tactic can be applied to online learning with tools (such as Polls, Like buttons, Mic and Chat functions) especially in Academic Literacy where student expression is so important. Not only is there a shift in the power dynamic in a classroom, but students experience a sense of community which increases engagement, as well as vital academic literacy skills. Thus, this paper seeks to demonstrate how a control-sensitive classroom can enhance student engagement and success in an online academic literacy classroom by analysis of student perspectives through qualitative and quantitative data.